2020
DOI: 10.3390/ijerph18010213
|View full text |Cite
|
Sign up to set email alerts
|

A Two-Year Longitudinal Study of the Association between Oral Frailty and Deteriorating Nutritional Status among Community-Dwelling Older Adults

Abstract: Background: Limited longitudinal studies exist to evaluate whether poor oral health and functions affect the incidence of deteriorating nutritional status. We investigated if there were longitudinal associations between oral frailty, defined as accumulated deficits in oral health, and deteriorating nutritional status among community-dwelling older adults. Methods: The study population consisted of 191 men and 275 women (mean age, 76.4 years) from the Takashimadaira Study. Multifaced oral health assessment was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
38
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 41 publications
4
38
0
1
Order By: Relevance
“…This study revealed a significant association between oral hypofunction and sarcopenia, even after adjusting for effects of multiple variables. Numerous studies have shown that decreased oral function leads to poor nutritional status [ 9 , 20 , 49 ]. It has also been suggested that a decrease in oral function affects the choice of food intake [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study revealed a significant association between oral hypofunction and sarcopenia, even after adjusting for effects of multiple variables. Numerous studies have shown that decreased oral function leads to poor nutritional status [ 9 , 20 , 49 ]. It has also been suggested that a decrease in oral function affects the choice of food intake [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gait speed, a subdomain of physical frailty, was significantly associated with oral frailty. Oral frailty may cause physical frailty, as the former may affect nutritional status among older adults and lead to weight loss [8]. Xue et al have suggested a frailty cycle model, whereby weight loss leads to weakness, exhaustion, and low gait speed [2].…”
Section: Discussionmentioning
confidence: 99%
“…Oral frailty is defined as poor oral status that increases the risk of physical frailty, sarcopenia, long-term care needs, and premature mortality [5]. Moreover, oral frailty has been associated with social frailty and malnutrition, both of which increase the risk of physical frailty [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that poor oral health is closely associated with adverse health outcomes [ 16 , 20 , 21 ]. Malnutrition is attributed to poor oral status and function [ 15 , 22 ], resulting in sarcopenia and physical frailty [ 11 , 12 , 13 , 14 ]. Malnutrition has been considered the indirect effect of poor oral health on systemic condition.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that these functions are also impaired by aging and poor oral management, known as oral frailty, oral sarcopenia, and oral hypofunction [ 16 , 17 , 18 , 19 , 20 ]. The adverse effects of a decline of these functions on systemic and nutritional status have been reported [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. Conversely, occlusal support is also important in oral functions, especially mastication [ 23 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%